Enhanced vitamin K expenditure as a major contributor to vitamin K deficiency in COVID-19. (December 2022) - Visser, Margot P.J.; Walk, Jona; Vermeer, Cees; Bílková, Simona; Janssen, Rob; Mayer, Otto
Highlights: Vitamin K deficiency is associated with worse clinical outcome in COVID-19 patients. High levels of inactive MGP reflect vitamin K insufficiency, and vice versa . Inflammation-induced vitamin K usage may be the reason for vitamin K deficiency in COVID-19. Normal inactive MGP levels prior to COVID-19 infection support this theory. Abstract: Objectives: Vitamin K deficiency consistently associates with worse clinical outcome in COVID-19 patients. However, whether this is due to increased expenditure during inflammation or poor vitamin K status prior to infection remained unknown. Methods: Dp-ucMGP levels of 128 individuals were measured for the post-MONICA study and were compared to SARS-CoV-2 PCR testing results. Results: Dp-ucMGP levels prior to COVID-19 infection were not significantly different comparing PCR-negative, PCR-positive and not hospitalized, and PCR-positive and hospitalized patients. Conclusion: In this study, we demonstrate normal vitamin K status prior to infection in SARS-CoV-2 positive patients, supporting the theory of increased utilisation during disease.